LBD18 uses a dual mode of a positive feedback loop to regulate ARF expression and transcriptional activity in Arabidopsis. (17th June 2018) - Pandey, Shashank K.; Lee, Han Woo; Kim, Min‐Jung; Cho, Chuloh; Oh, Eunkyoo; Kim, Jungmook
Summary: A hierarchy of transcriptional regulators controlling lateral root formation in Arabidopsis thaliana has been identified, including the AUXIN RESPONSE FACTOR 7 ( ARF7 )/ ARF19‐LATERAL ORGAN BOUNDARIES DOMAIN 16 ( LBD16 )/ LBD18 transcriptional network; however, their feedback regulation mechanisms are not known. Here we show that LBD18 controls ARF activity using the dual mode of a positive feedback loop. We showed that ARF7 and ARF19 directly bind AuxRE in the LBD18 promoter. A variety of molecular and biochemical experiments demonstrated that LBD18 binds a specific DNA motif in the ARF19 promoter to regulate its expression in vivo as well as in vitro . LBD18 interacts with ARFs including ARF7 and ARF19 via the Phox and Bem1 domain of ARF to enhance the transcriptional activity of ARF7 on AuxRE, and competes with auxin/indole‐3‐acetic acid (IAA) repressors for ARF binding, overriding the negative feedback loop exerted by Aux/IAA repressors. Taken together, these results show that LBD18 and ARF s form a double positive feedback loop, and that LBD18 uses the dual mode of a positive feedback loop by binding directly to the ARF19 promoter and through the protein–protein interactions with ARF7 and ARF19. This novel mechanism of feedback loops may constitute a robust feedback mechanism that ensures continued lateral root growth in response to auxin in Arabidopsis. Significance Statement: Despite our knowledge of the gene regulatory networks of lateral root formation, the feedback regulation mechanism of the ARF ‐ LBD s gene networks is unknown. We show that LBD18 and ARFs form a double positive feedback loop and that LBD18 utilizes the dual mode of a positive feedback loop by binding directly to the ARF19 promoter and through the protein‐protein interactions with ARFs, providing a robust feedback mechanism for sustained lateral root formation in response to auxin.